2011
DOI: 10.1128/mcb.05160-11
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Basigin Isoforms and the Inhibitory Function of Basigin-3 in Human Hepatocellular Carcinoma Proliferation and Invasion

Abstract: Basigin, which has four isoforms, plays an important role in invasion of hepatocellular carcinoma (HCC).Detailed transcriptional regulation and functions of the basigin isoforms have not been reported except in the case of the predominant isoform basigin-2, which act as inducer of matrix metalloproteinases (MMPs). Here we determined that basigin-2, basigin-3, and basigin-4 were the most abundant transcript variants in human cell lines. GeneRacer PCR and luciferase reporter assays showed that basigin-3 and basi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
91
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(91 citation statements)
references
References 45 publications
0
91
0
Order By: Relevance
“…Several studies have clearly shown a key role for CD147 in tumor progression and metastasis. Indeed, high CD147 expression levels have been reported in many tumors, including breast cancer, lymphoma, oral squamous cell carcinoma, glioma, melanoma, lung, bladder, liver, and kidney carcinomas (5)(6)(7). Accordingly, CD147 expression has been associated with known risk factors for breast cancer and with poor prognosis in patients with breast cancer (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have clearly shown a key role for CD147 in tumor progression and metastasis. Indeed, high CD147 expression levels have been reported in many tumors, including breast cancer, lymphoma, oral squamous cell carcinoma, glioma, melanoma, lung, bladder, liver, and kidney carcinomas (5)(6)(7). Accordingly, CD147 expression has been associated with known risk factors for breast cancer and with poor prognosis in patients with breast cancer (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Anti-CD147 mAb was prepared by our laboratory (7). Primary antibodies against Sp1, c-Myc, or tubulin were from Santa Cruz.…”
Section: Western Blot Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…It is usually expressed at low levels in most normal tissues, but is highly upregulated during dynamic cellular events, such as tissue remodeling and cancer progression (Gabison et al, 2009;Nabeshima et al, 2006;Yan et al, 2005). Emmprin was originally identified as a cell surface factor that induces MMP production in stromal cells (Ellis et al, 1989;Kataoka et al, 1993), but later studies revealed that emmprin is identical to basigin-2 (Biswas et al, 1995;Liao et al, 2011), and is multifunctional; it is now widely known as CD147. CD147 induces several MMPs at both the mRNA and protein level, including MMP1, MMP2, MMP3, MMP9, MT1-MMP and MT2-MMP, although there is variation in the particular MMPs induced in different systems Yan et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…(7) Functional analyses have revealed the involvement of CD147/basigin in energy metabolism, reproduction, development, and tumor invasion. (8) To discover novel cell surface molecules expressed on hESCs, we generated a panel of monoclonal antibodies (MAbs) against undifferentiated hESCs using the mouse medial iliac lymph node method. This study describes the biochemical characterization and identification of the hESC surface molecule that is recognized by MAb2.…”
Section: Introductionmentioning
confidence: 99%